2014
DOI: 10.1111/gcbb.12138
|View full text |Cite
|
Sign up to set email alerts
|

Soil carbon balance following conversion of grassland to oil palm

Abstract: Oil palm (Elaeis guineensis Jacq.) crops are expanding rapidly in the tropics, with implications for the global carbon cycle. Little is currently known about soil organic carbon (SOC) dynamics following conversion to oil palm and virtually nothing for conversion of grassland. We measured changes in SOC stocks following conversion of tropical grassland to oil palm plantations in Papua New Guinea using a chronosequence of plantations planted over a 25-year period. We further used carbon isotopes to quantify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 46 publications
2
24
0
Order By: Relevance
“…Studies of the effects of conversion of forests to oil palm plantations are not only sparse, but also contradictory. Accordingly, some studies have reported a soil organic carbon (SOC) stock decrease (Sommer et al 2000, Hergoualc'h and Verchot 2011, Bruun et al 2013, Chiti et al 2014 or increase (Frazao et al 2013, Goodrick et al 2015 or no change (Tanaka et al 2009, Khasanah et al 2015 following land use conversion to oil palm. These studies mostly focus on the effects of conversion of primary forests to smallscale oil palm plantations, but not to large-scale oil palm plantations that may differ in organic matter management and replantation technique and are, moreover, often the point of the debate regarding deforestation and environmental degradation in tropical areas.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the effects of conversion of forests to oil palm plantations are not only sparse, but also contradictory. Accordingly, some studies have reported a soil organic carbon (SOC) stock decrease (Sommer et al 2000, Hergoualc'h and Verchot 2011, Bruun et al 2013, Chiti et al 2014 or increase (Frazao et al 2013, Goodrick et al 2015 or no change (Tanaka et al 2009, Khasanah et al 2015 following land use conversion to oil palm. These studies mostly focus on the effects of conversion of primary forests to smallscale oil palm plantations, but not to large-scale oil palm plantations that may differ in organic matter management and replantation technique and are, moreover, often the point of the debate regarding deforestation and environmental degradation in tropical areas.…”
Section: Introductionmentioning
confidence: 99%
“…The grasslands showed the highest total soil organic C stock compared to the other land use systems due to the greater ability of grasslands to produce diverse aboveground biomass (Pinheiro et al, 2010) or due to the addition of recalcitrant black C during burning operations (Goodrick et al, 2015). Natural and restored grasslands are effective vegetation types for SOC sequestration due to the higher carbon input from the roots (Wei et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Soil C exists primarily in three chemical forms, although few attempts have been made to fractionate C based on its faunal oxidation potential or the ecosystem services it renders (Grandy and Robertson, 2007;Berreto et al, 2011). The chemical components of soil C are primarily elemental C (e.g., charcoal, graphite and soot) from geological or biomass burning sources, inorganic C that is derived from geologic or soil mineral sources, such as carbonates (e.g., calcite and dolomite), and organic C from the natural decomposition of plants and animals (Goodrick et al, 2015). Several methods are available for assessing soil C stocks; dry combustion analyzers are the most widely used.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, Huang et al (2010), mentioned that over the years, grasslands lose their vocation to accumulate SOC due to a decrease in the system productivity, mainly due to an increasing degradation of its properties, motivated by cattle overgrazing and the type of grassland established. Accordingly to Goodrick et al (2015), some tropical agroforestry systems slowly reduce the SOC content due to the higher N contents that legumes procure (which speeds up the mineralization processes). In addition, a higher STN concentration and higher mineralization, reduces the C/N ratio, resulting in a greater SOM decomposition.…”
Section: Soil Biochemistry Propertiesmentioning
confidence: 99%